Hemoglobin A1c (Hba1c) is Strongly Correlated with Mean Corpuscular Volume Among Type 2 Diabetes Mellitus (T2dm) Patients Admitted in a Tertiary Hospital in East Java, Indonesia - Salim, Yusuf; Kalanjati, Viskasari P.; Prajitno, Jongky H.; Melbiarta, Rezy R. (Folia Medica Indonesiana, 2022)
Highlight: • Moderate negative significant correlation between HbA1c and MCV levels in T2DM was yet reported widely. • MCV levels could mirror health indicator in adult T2DM patients. Abstract: HbA1c showed the average level of blood sugar in the recent 2-3 months. This parameter can be used to help physicians to diagnose T2DM and to plan appropriate treatment. Meanwhile, the mean corpuscular volume (MCV) is established from the erythrocytes levels as one of the blood corpuscles, in which hemoglobin is bound to. We hypothesize that MCV is correlated to the HbA1c levels and could be an indicator of blood sugar levels in adult T2DM patients. A retrospective cross-sectional study based on the medical record of patients admitted to the Outpatient Section of Department of Internal Medicine, Dr. Soetomo General Academic Hospital, Indonesia from January to December 2019 was done. Patients under 18-years old, and incomplete medical record data were excluded. Adult patients diagnosed with T2DM and have been received initial treatment in this section were included (n=1.688). Data was analyzed using correlation test in SPSS 17.0 (USA), p-value less than 0.05 was considered significant. We found a significant negative correlation between HbA1c and MCV levels in these patients (r=-0.312; p<0.001). MCV levels showed a paradoxical pattern against the blood glucose levels in T2DM and could serve as the health indicator in these patients.